Characteristic of Chronic Kidney Disease Patients with Haemodialisa - Anna Tirawani Ambarita; Teja Kusuma Aisyah; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2026)
Chronic kidney failure is a progressive and irreversible decline in kidney function, and it is one of the catastrophic diseases with high financial burden in Indonesia. The increase in chronic kidney failure cases is influenced by the prevalence of hypertension, diabetes mellitus, obesity, as well as changes in community lifestyle. This study aims to identify the characteristics of chronic kidney failure patients undergoing hemodialysis in North Sumatra Province from 2015 to 2020 based on gender, age, type of National Health Insurance membership, and average service claim costs. The study uses a descriptive quantitative approach with a non-experimental cross-sectional design. The data used are secondary data of a 1% sample from BPJS Kesehatan for 2015–2020, which has obtained data usage permission from the BPJS Kesehatan Central Office. The variables analyzed include gender, age, membership segmentation, diagnosis, and claim verification costs.Keywords: chronic kidney disease, hemodialysis, BPJS Kesehatan, claim cost, patient characteristics. The analysis was carried out descriptively by taking into account individual weights to reflect the population. The study results showed that the proportion of chronic kidney failure patients undergoing hemodialysis was mostly male, totaling 66.17 percent. Based on age, the adult group (19–59 years) dominated with 67.79 percent, followed by the elderly proportion at 28.07 percent. The largest proportion by type of participation came from the PBPU group at 62.05 percent, followed by PPU at 17.29 percent. The average cost of chronic kidney failure claims with hemodialysis was Rp816.713,9 with a standard deviation of Rp209.344,8, a minimum claim of Rp95.900, and a maximum of Rp4.219.800. Chronic kidney failure patients in North Sumatra were dominated by the productive age group, males, and PBPU participants, with a fairly high financial burden on the health insurance system. These findings indicate the need to strengthen promotive and preventive efforts against risk factors for chronic diseases to curb the increase in cases and the burden of health care costs